Health-related professional competence of physical education teachers: Narrative review and heuristic model - Lohmann, Julia; Hapke, Julia; Töpfer, Clemens (Swiss Journal of Educational Research, 2023)
Physical education (PE) is one setting in which pupils may acquire knowledge and skills to lead physically active lives. PE teachers play a key role in fostering respective health-related competences in pupils. For this, they themselves need appropriate professional competences. The purpose of this article is to highlight research trends on, and to propose a heuristic model for PE teachers’ health-related professional competence. Research trends and gaps are identified by a narrative literature review. The heuristic model describes several knowledge domains, beliefs, motivational orientations, and self-regulation as subdimensions of health-related professional competence. It is intended to provide an overview of important competence aspects and to serve as an orientation for further work.